Comparison of the eficiency of prolonged ultrasound-guided erector spinae plane block and prolonged epidural anesthesia in minimally invasive coronary bypass surgery - A. V. Stukalov; R. E. Lakhin; E. Yu. Garbuzov; E. N. Ershov; N. V. Stukalov (Вестник анестезиологии и реаниматологии, 2023)
The objective of the study was to evaluate the effectiveness of prolonged ESP-block in comparison with prolonged thoracic epidural anesthesia in MIDCAB surgery.   Materials and methods. We conducted a prospective randomised two centre study with 45 patients who underwent MIDCAB surgery. In addition to general anesthesia, prolonged ESP-block was performed in group 1 (n = 22), and prolonged epidural anesthesia was performed in group 2 (n = 23).   Results. The decrease in blood pressure caused by the development of the regional block at all stages of anesthesia was more pronounced when using epidural anesthesia. In group 2, the dosage of norepinephrine was higher: 0.06 (0.05; 0.0725) mcg/kg–1/min–1 in group 1 and 0.16 (0.16; 0.16) mcg/kg/min in group 2, p < 0.001. The duration of prolonged mechanical ventilation in group 1 was lower and amounted to 102.5 (90; 110) minutes versus 110 (110; 115) minutes in group 2. The duration of surgery did not differ between the groups, the fentanyl consumption for anesthesia was higher in group 1: 0.7 (0.6; 0.8) mg versus 0.6 (0.5; 0.1) mg in group 2 (p < 0.001). Postoperatively, pain was rated as mild to moderate in both groups, with less pain in the group with epidural analgesia at stages 4 to 32 hours at rest and on coughing. After 48 hours, there were no statistical differences between the groups. The score of pain during coughing in both groups did not exceed 3 points, and patients did not need emergency analgesia.   Conclusion. In MIDCAB operations, the prolonged ESP-block is an effective method of regional anesthesia. While providing a sufficiently high level of analgesia, the use of the ESP-block during surgery only slightly increases the fentanyl usage. In the postoperative period, when using the ESP-block, extubation occurs earlier, and analgesia is almost as good as epidural blockade.